1993
DOI: 10.1097/00001888-199301000-00012
|View full text |Cite|
|
Sign up to set email alerts
|

Problem-based learning

Abstract: The effects of problem-based learning (PBL) were examined by conducting a meta-analysis-type review of the English-language international literature from 1972 to 1992. Compared with conventional instruction, PBL, as suggested by the findings, is more nurturing and enjoyable; PBL graduates perform as well, and sometimes better, on clinical examinations and faculty evaluations; and they are more likely to enter family medicine. Further, faculty tend to enjoy teaching using PBL. However, PBL students in a few ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,843 publications
(215 citation statements)
references
References 0 publications
6
154
1
3
Order By: Relevance
“…This may reflect the introductory nature of the course, and the fact that the participation exercise was only 6% of their final grade. The absence of a beneficial effect on PBL grade outcomes in comparison to traditional methods supports previous studies that have found that PBL does not increase a student's knowledge of the course material (Albanese & Mitchell, 1993;Larin, Bucciere, & Wessel, 2010;Vernon & Blake, 1993). Klegeris & Hurren (2011) point out, however, that most studies measuring course outcomes are based on observations in small class sizes.…”
Section: Grade Outcomessupporting
confidence: 76%
“…This may reflect the introductory nature of the course, and the fact that the participation exercise was only 6% of their final grade. The absence of a beneficial effect on PBL grade outcomes in comparison to traditional methods supports previous studies that have found that PBL does not increase a student's knowledge of the course material (Albanese & Mitchell, 1993;Larin, Bucciere, & Wessel, 2010;Vernon & Blake, 1993). Klegeris & Hurren (2011) point out, however, that most studies measuring course outcomes are based on observations in small class sizes.…”
Section: Grade Outcomessupporting
confidence: 76%
“…Similarly, Albanese (2000) quoted that information-processing theory propagated by Schmidt (1983) emphasised the importance of information processing in tapping the students' prior knowledge. Schmidt also stressed how past learning may affect the present learning experience.…”
Section: Theoretical and Conceptual Framework Used In The Module Devementioning
confidence: 99%
“…Conclusions from papers researching this topic have either been inconclusive or inconsistent [63]. This inconsistency is partly due to there not being a definitive definition for PBL since its creation over 40 years ago [64].…”
Section: Traditional Medical Curriculum (Tmc) Problem Based Learningmentioning
confidence: 99%